Strength Analysis of Betelnut Fiber-Reinforced Resin Composite - Fahmi, Hendriwan; Hadi, Syafrul; Kapur, Fajar Marda (Jurnal Teknik Mesin (JTM), 2016)
Material is needed in life, the material itself is used aims to facilitate human activities, in the development of modified human material in various ways, one of which composite materials. Composite is a combination of two or more elements that get combined properties of the elements combined. Liquid Epoxy resin is a low molecular weight organic group containing epoxide. The composite material used is a fiber reinforced resin nut shell. Point of this study is know tensile strength of fiber nut shell composite, variations in the composition of the epoxy resin and fiber nut shell made in this study was 90:10%wt, 80:20%wt,  and  70:30%wt,  fiber  length  of  2  cm  with  random  fiber  orientation.  This experiment is the tensile test. Tensile test was conducted to determine the tensile stress each - each composition, the standard used is ASTM 638 02. From the test results obtained on the composition of the composite tensile strength of 90: 10% wt is 9.8 MPa, the composition of 80: 20% wt was 13.06 MPa and the composition of 70: 30% wt is 14.04 MPa. Of the fracture surface can be seen that the fibers are well distributed and the bond between resin and fiber is also more evenly so that the tensile strength increased.